Security-Development Nexus : Exploring the Interplay between Security and Development of Baleh Dam towards the Iban in Sarawak - Jong Jing, Wen; Lucy, Sebli Seidelson (Secholian Publication., 2025)
Hydropower development has emerged as a key driver of sustainable progress in Malaysia, as demonstrated by the ambitious Baleh Dam project, underscoring the nation's dedication to renewable energy. This study primarily focuses on economic security. Therefore, this research scrutinizes the potential impact on the Iban community residing in Ulu Baleh, Kapit, from a human security perspective. The security-development nexus intricately examines the relationship between dam development and economic security of the affected community in Nanga Antawau especially the Iban in Baleh, Kapit. The Iban community's profound reliance on ancestral lands and rivers for sustenance and cultural identity renders them susceptible to displacement and resource loss. Previous large-scale dam projects have wreaked havoc on local communities, and the estimated 1,345 square kilometres of inundated land by the Baleh Dam raises concerns about human rights and well-being for the Iban. Moreover, this study underscores the multidimensional nature of the security concept, encompassing both traditional and non traditional threats. We will explore in-depth into the impacts on the Iban community's economic security. By doing so, this research contributes valuable insights to the ongoing discourse on security, development, and livelihood preservation. It emphasizes the imperative for sustainable progress that upholds the rights and interests of local communities. The findings of this paper illuminate the interrelationship between security and development, revealing that the 1,392-strong Iban community's right to access a peaceful livelihood and economic security is closely tied to the Baleh Dam, which has proven to be economically destructive in Nanga Antawau, Kapit, Sarawak.